Condicionamiento Operante De Sapajus Apella (2024)
The research on databases to focus the search for operant conditioning techniques in Sapajus apella centers on how these techniques can be applied as a method of preventive medicine to improve the management, diagnosis, and quality of life of these primates in captivity (Schneider & Ringuet, 2012). The research reviews various academic and scientific databases to identify studies that employ operant conditioning in primates, with a particular focus on capuchin monkeys (Sapajus apella) (Mendoza & Mason, 2000).